Use of geographical information systems to identify counties in Georgia with high risk for childhood lead poisoning - R. Rustin; Christy Kuriatnyk; Byron Lobsinger; Simone Charles (Georgia Southern University, 2015)
Background: For children in Georgia, lead poisoning is a substantial public health problem. Primary risk factors include low socioeconomic status and poor-quality housing built prior to 1978. The Environmental Health Team of the Georgia Department of Public Health (DPH) utilized geographical information system (GIS) technology and census housing data to identify counties in which children have high risk for lead poisoning. The purpose of this research was to update and refine previous maps developed with older technology and on a different geographic scale so that targeted public health interventions can be developed. Methods: Data related to stratified and median housing age data were derived from the 2013 5-year American Community Survey. With ESRI ArcMap 10.2 geographic information software, the data were geospatially linked to the state's county shapefile for development of spatial maps. Results: A series of spatial maps were developed utilizing housing risk factors of age and occupancy status. Refined spatial maps were developed for: 1) the percentage of homes built prior to 1978 and prior to 1950 per county; 2) owner- and renteroccupied housing stratified by age and color-coded per county; and 3) counties in which children were at high risk for lead poisoning. Conclusions: The data from this research provides information for the DPH Lead and Healthy Homes program of areas in the state where targeted interventions are needed. The updated maps can be used to educate policy makers, healthcare providers, and community leaders in regard to prevention of lead poisoning.